2020
DOI: 10.1177/0361198120966602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Relationships between Perception-Reaction Times, Emergency Deceleration Rates, and Crash Outcomes using Naturalistic Driving Data

Abstract: Perception-reaction time (PRT) and deceleration rate are two key components in geometric design of highways and streets. Combined with a design speed, they determine the minimum required stopping sight distance (SSD). Current American Association of Highway Transportation Officials (AASHTO) SSD guidance is based on 90th percentile PRT and 10th percentile deceleration rate values from experiments completed in the mid-1990s. These experiments lacked real-world distractions, and so forth. Thus, the values from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…With regard to deceleration rate, previous studies have indicated that different deceleration rates affect the braking response time of following drivers [ 15 , 19 ]. Wood and Zhang [ 27 ] reported that the minimum and maximum deceleration rates among 2971 natural drivers were 0.23 g and 1.09 g, respectively. These represent the minimum and maximum deceleration rates that a driver may experience during normal daily driving.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to deceleration rate, previous studies have indicated that different deceleration rates affect the braking response time of following drivers [ 15 , 19 ]. Wood and Zhang [ 27 ] reported that the minimum and maximum deceleration rates among 2971 natural drivers were 0.23 g and 1.09 g, respectively. These represent the minimum and maximum deceleration rates that a driver may experience during normal daily driving.…”
Section: Methodsmentioning
confidence: 99%
“…First, the RoI in target spots is split into 12 zones for vehicle (horizontal) and pedestrian (vertical). In our experiment, we set 𝑡 𝑗 as 1, 2, and 3 (after 1 sec, 2 sec, and 3 sec) based on PIEV (perception-intellection-emotion-volition) theory in accident [37]- [40]. PIEV is the amount of time it takes a driver to react to a hazard, and each step is time to discern an object or event, to understand the implications of the situation, to decide how to react, and to initiate the action (engaging the brakes), respectively.…”
Section: Figure 12 Average Speed Of Vehicles By Frames In Each Test Spotmentioning
confidence: 99%
“…PIEV is the amount of time it takes a driver to react to a hazard, and each step is time to discern an object or event, to understand the implications of the situation, to decide how to react, and to initiate the action (engaging the brakes), respectively. Much research has been conducted on PIEV time, and designed various time ranges for safe, 1.48 to 2.5 seconds [38]- [40]. ASSHTO (The America Association State Highway and Transportation Officials) recommended to secure 2 till 2.5 seconds [37].…”
Section: Figure 12 Average Speed Of Vehicles By Frames In Each Test Spotmentioning
confidence: 99%
“…These factors are directly related to MWL and can affect the mean speed and PRT. It is worth noting that Wood et al developed a prediction model that accounts for the dynamic relationship between speed, PRT, and deceleration rate using crash and conflict data (49). This is a new area of research with a huge potential to enrich our understanding of the 'true' failure mechanism.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Additionally, future work may utilize naturalistic data to enrich the current knowledge of these relationships. These complex relationships will be further complicated if one considers the effect of new technologies such as collision warning systems or as vehicles exhibit an increased level of automation (49).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%